PENGARUH KOMPETENSI PEDAGOGIK DAN KOMITMEN GURU TERHADAP KINERJA GURU DIMODERASI GAYA KEPEMIMPINAN KEPALA SEKOLAH DI SMP NEGERI SE KECAMATAN PATI - Nur Rahayu, 12.5202.0158; Mindarti, Cicilia Sri (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aimed to examine the effect of teachers pedagogical competence and commitment to performance throughout the District Junior High School teacher Pati. Intake of respondents conducted by random sampling stratifiled proportionale 189 oran using questionnaire data, after the data is processed using a statistical technique to test the validity of the component matrix, Cronbach alpha reliability test, normality test with a non-parametrix KS, multiple regression analysis, F test, r² test with adjusted r-square and t test. The results showed pedagogical positive and significant effect on the performance of teachers, teacher commitment and significant positive effect on the performance of teachers, principals leadership style positive and significant effect on the performance of teachers, principals leadership style moderates the influence of teachers pedagogical competence on performance positively and significantly , the principals leadership style moderates the influence of teachers commitment to teacher performance negatively and significantly on teacher performance. Keywords: Pedagogical Competence, Commitment Teacher, Principal Leadership Style, Performance Master